New Power System Based on Renewable Energy in the Context of Dual Carbon - Liang Ning; Tianmeng Yuan; Haotian Wu (International Transactions on Electrical Energy Systems)
Energy is the basic driving force to promote the economic development of all countries in the world. In the face of the era of great changes unseen in a century, the world is actively deploying and developing renewable energy. However, these forms of new energy power generation are characterized by intermittency and randomness, and their unstable power characteristics and uncontrollable source capacity have negative consequences for the secure and stable operation of the electricity system. Therefore, once new energy sources are incorporated on a large scale, system reliability studies are required. The mission of the new electricity system with new resources as the main source is to adapt to the development of large-scale renewable energy and solve the three major problems of shortage of existing energy and power, pollution, and safety. In comparison to conventional electrical systems, the new power system is not a simple replacement but a revolution. Therefore, this paper studied a new type of power system based on renewable energy. Through experiments, it is concluded that the new electricity system with renewable energy sources is not only more environmentally friendly but also can save 10.5% of electricity costs and greatly improve the utilization rate of available energy.